Mechanochemical synthesis of MgTa2O6 ceramic - (:unkn) unknown (ELSEVIER SCI LTD, 2009)
MgTA(2)O(6) powders were prepared by mechanochemical synthesis from MgO and Ta2O5 in a planetary ball mill in air atmosphere using steel vial and steel balls. High-energy ball milling gave nearly single-phase MgTa2O6 after 8 h of milling time. Annealing of high-energy milled powder at various temperatures (700-1200 degrees C) indicated that high-energy milling speed up the formation and crystallization of MgTa2O6 from the amorphous mixture. The powder derived from 8 h of mechanical activation gave a particle size of around 28 nm. Although at low-annealing temperatures the grain size was almost the same as-milled powder, the grain size increased with annealing temperature reaching to around 1-2 mu m after annealing at 1200 degrees C for 8 h. (C) 2008 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: X-ray methods; MgTa2O6; Mechanochemical synthesis; High-energy milling; MICROWAVE DIELECTRIC-PROPERTIES; FREQUENCIES